Penyuluhan Kesehatan dan Pemeriksaan kadar Gula Darah untuk Skrining Diabetes Melitus - Puji Lestari, Mardiana; Padmasari, Siwi; Marchaban (The Journal of Innovation in Community Empowerment, 2024)
Diabetes mellitus (DM) is a disease that is a global health problem whose numbers continue to increase. DM has the highest prevalence and causes more severe disease complications such as heart disease and stroke, which often cause death throughout the world. Proper prevention and treatment will reduce the impact or risk of unwanted complications. This health education activity was carried out to increase public knowledge and understanding about DM disease and how to screen to detect DM disease among residents of Pangkah Hamlet. The extension activity method begins with giving a pretest, then continues with the delivery of material and discussion, then ends with a posttest. Next, a health examination is carried out, namely measuring blood glucose levels. Extension activities are carried out in five stages: preparation of location surveys, preparation and preparation of proposals, implementation, evaluation, and reporting. The preparation stage for a location survey consists of field observations. The preparation and proposal preparation stage consists of collecting material, preparing the proposal, and preparing the material. The stages of implementing the activities are pretest, counseling material, and discussion. The evaluation stages include posttest and report preparation. The target of this activity is women residents of Pangkah hamlet Sumberagung, Jetis, Bantul, and Yogyakarta. The results of the participants knowledge test about DM before and after the activity were carried out, with good results increasing from 83.33% to 100%, with an average pretest score of 81.67 and posttest score of 93.61. The results of the blood sugar level screening (GDS) showed that the majority were below 200 mg/dl, namely 34 participants (94.44%). From these results, it can be concluded that this community service activity was able to increase knowledge about DM among women residents of Pangkah hamlet and the results of the initial DM screening were in the normal range.